Elevated circulating GPHB5 levels in women with insulin resistance and polycystic ovary syndrome: A cross-sectional study and multiple intervention studies - Wang, Yanping; Xiang, Ting; Xia, Xuyun; Zhang, Hongmin; Geng, Shan; Yang, Gangyi; Qiu, Sheng; He, Yirui; Liu, Rui; Li, Ling; Liu, Hua; Li, Ke; et al. (Frontiers in Endocrinology, 2022)
Objective: GPHB5 has been found to be associated with glucose and lipid metabolism in animal studies. However, the association of GPHB5 with IR and metabolic disorders remains unknown, and there is a lack of research in humans. Our aim in this study was to investigate the relationship between circulating GPHB5 and metabolic disorders in humans. Methods: Bioinformatics analysis was performed to understand the relationship between GPHB5 and metabolic disorders. GPHB5 mRNA expression in mice and rats was determined using RT-qPCR. Circulating GPHB5 concentrations were measured with an ELISA kit. EHC and OGTT were performed in humans. Results: Bioinformatics analysis shows that GPHB5 is associated with metabolic disorders and PCOS. GPHB5 mRNA expression levels in the metabolic-related tissues of HFD-fed mice, db/db and ob/ob mice, and PCOS rats were significantly higher than those of WT mice or rats. In human studies, we find that circulating GPHB5 levels were significantly higher in women with IR and PCOS. GPHB5 levels were positively correlated with age, BMI, WHR, BP, FBG, 2 h-BG, FIns, 2 h-Ins, TC, LDL-C, HbA1c, and FFA, but negatively correlated with adiponectin. Furthermore, GPHB5 was positively correlated with DHEAS and FAI, while negatively correlated with SHBG, FSH, SHBG and FSH. The increased GPHB5 concentration was related to IR and PCOS. After the treatment of metformin, GLP-1RA (Lira), and TZDs, circulating GPHB5 levels were decreased. Conclusions: Our results reveal that circulating GPHB5 could be a biomarker and potential therapeutic target for IR and PCOS in women.